Description of Perceptions of Neonatology Nurses in the Implementation of Assessment and Management of Pain in Neonates - Nugraha, Puput; Fitri, Siti Yuyun Rahayu; Maryam, Nenden Nur Asriyani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Neonates with complications admitted to the Neonatal Intensive Care Unit (NICU) must receive various invasive actions that cause negative impacts, one of which is pain. The limited growth and development of neonates causes pain to be objective depending on the nurse's perception. As a result, pain is not managed properly and has a high risk of causing negative impacts for neonates. Objective: This study aims to identify the perception of neonatology nurses in the implementation of pain assessment and management in neonates. Method: This study used descriptive quantitative research with a cross-sectional time approach to neonatology nurses who were collected in pediatric nurse organizations in the West Java region using a convenience sampling technique. The instrument used was The Nurses' Attitudes and Perceptions of Pain Assessment in Neonatal Intensive Care Questionnaire (NAPPAQ). Results: The results of the study with a total of 72 respondents, 50% of respondents strongly agreed on the importance of pain assessment, and 48.6% strongly agreed on the importance of using pain assessment tools. The assessment tools that are often used in assessing pain are NIPS (72.2%), and non-pharmacological pain management that is often given is physical methods. Conclusions: Although most nurses agree on the importance of pain assessment, in practice there are still nurses who assess pain without using clear assessment tools.